Isolation and characterization of phage ISTP3 for bio-control application against drug-resistant Salmonella - Islam, Md. Sharifull; Nime, Ishatur; Pan, Fan; Wang, Xiaohong (Frontiers in Microbiology, 2023)
Salmonella including drug-resistant strains are major foodborne pathogens causing serious illness and pose a great threat to the prevention and control for food safety. Phages can naturally defect the bacterium, is considered as a new and promising biological antimicrobial agent in the post-antibiotic era. A poultry facility in Wuhan, China provided wastewater samples from which a collection of 29 phages were isolated and purified. A broad host spectrum phage ISTP3, which capable of infecting all tested Salmonella, including drugresistant Salmonella enterica, were examined. Additionally, the effectiveness of this phage ISTP3 in reducing drug-resistant S. enterica was assessed in diverse food samples.Transmission electron microscopy (TEM) and whole genome sequencing demonstrated that ISTP3 was found to belong to family Ackermannviridae. The one-step growth experiment and assays of stability demonstrated that ISTP3 exhibited short periods of inactivity before replicating, produced a significant number of viral progeny during infection, and remained high stable under varying pH and temperature conditions. We evaluated the efficacy of phage ISTP3 against drug-resistant Salmonella on chicken breast and lettuce samples at different temperatures. When applying phage ISTP3 in food matrices, the drug resistant Salmonella count significantly reduced at 4 °C and 25 °C at an MOI of 100 or 1000 within a timescale of 12 h. Overall, the results, such as broad host ranges, strictly lytic lifestyles, absence of lysogenic related genes, toxin genes, or virulence genes in the genome, demonstrate that the application of phage ISTP3 as a biocontrol agent has promising potential for preventing and controlling drug-resistant S. Typhimurium in the context of food safety, processing, and production.